2016
DOI: 10.1002/2016jc012040
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface wind streaks in spaceborne synthetic aperture radar imagery

Abstract: Wind streaks are often observed in Synthetic aperture radar (SAR) images. They are used to determine the sea surface wind direction for sea surface wind field retrievals. It is generally understood that visible wind streaks are caused by roll vortices in the marine atmospheric boundary layer. In this study, 227 X‐band spaceborne SAR images of TerraSAR‐X and TanDEM‐X acquired from the three FiNO platforms in the North Sea and Baltic Sea were thoroughly analyzed for a comprehensive understanding of the manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
5
18
0
Order By: Relevance
“…However, both FFT and LG wind direction retrieval methods are limited when there is a lack of wind streaks imaged by the SAR, especially at low wind speeds; one study indicated that MABL rolls were present in 44% of 1882 SAR images and completely absent in 34% [18]. Furthermore, in another recent study, ∼48.0% of a data set of 227 SAR images displayed wind streaks; among those images, 67.3%, 20.0%, and 12.7% occurred under unstable, neutral, and stable atmospheric conditions, respectively [19]. As mentioned above, these studies only focus on wind direction estimation under low to medium wind speed conditions, and they do not take into account the radar backscatter dependence on incidence angle.…”
Section: Introductionmentioning
confidence: 99%
“…However, both FFT and LG wind direction retrieval methods are limited when there is a lack of wind streaks imaged by the SAR, especially at low wind speeds; one study indicated that MABL rolls were present in 44% of 1882 SAR images and completely absent in 34% [18]. Furthermore, in another recent study, ∼48.0% of a data set of 227 SAR images displayed wind streaks; among those images, 67.3%, 20.0%, and 12.7% occurred under unstable, neutral, and stable atmospheric conditions, respectively [19]. As mentioned above, these studies only focus on wind direction estimation under low to medium wind speed conditions, and they do not take into account the radar backscatter dependence on incidence angle.…”
Section: Introductionmentioning
confidence: 99%
“…Mouche et al [24] also proposed another PR model that is dependent on both the incidence angle and the azimuth angle, as shown in Equation (8). For each azimuth angle, the dependence of PR on the incidence angle follows an exponential relationship, as shown in Equation (9). The coefficients C , C and C in Equation 8correspond to the upwind, crosswind and downwind directions (Equations (10) to (12)), respectively.…”
Section: Development Of the Pr Model For Gf-3 Qps Hh Polarization Datamentioning
confidence: 99%
“…Following this rationale, SSW directions have been derived from images acquired by various spaceborne SAR missions, e.g., ERS/SAR, ENVISAT/ASAR and TerraSAR-X, using either the fast Fourier transform (FFT) method [5] or the local gradient (LG) method [6,7]. Interestingly, approximately 50% of spaceborne SAR images present clear wind streaks [8,9]. The appearance of wind streaks in SAR images is a complicated issue that is related to thermal convection, inflection point and wind shear under unstable and stable atmospheric situations [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR images of the sea provide evidence of a large set of geophysical phenomena: besides oceanographic features related to wind waves and swell, ocean internal waves and sea currents, atmospheric phenomena related to the wind rolls [3][4][5][6][7] and atmospheric gravity waves [8], not all of them locally related each other. These phenomena have different spatial scales and spatial layouts, besides being located in different areas, and often are all present in a SAR image.…”
Section: Introductionmentioning
confidence: 99%